2010
DOI: 10.1017/s1461145710001082
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor signalling mediates antidepressant effects of lamotrigine

Abstract: The anticonvulsant drug lamotrigine has been shown to produce antidepressant effects in patients with bipolar disorder. To date, only a few preclinical studies have been conducted using lamotrigine treatment in the forced swim test (FST), an animal model of depression with low face validity. The underlying mechanisms by which lamotrigine works have not been well characterized either. This study extends earlier work on the role of brain-derived neurotrophic factor (BDNF) in regulating the antidepressant actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…Chronic stress and glucocorticoid administration may induce depressive effects in rats by lowering hippocampal BDNF levels (Smith et al, 1995;Hansson et al, 2003), whereas some antidepressants are reported to achieve their efficacy by increasing BDNF in the hippocampus (Li et al, 2011;Takano et al, 2012;Zhang et al, 2012). Although the underlying mechanisms remain unidentified, it has been reported that glucocorticoids can prevent synaptic function maturation through suppression of the BDNF-stimulated MAPK/ERK pathway (Kumamaru et al, 2011(Kumamaru et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress and glucocorticoid administration may induce depressive effects in rats by lowering hippocampal BDNF levels (Smith et al, 1995;Hansson et al, 2003), whereas some antidepressants are reported to achieve their efficacy by increasing BDNF in the hippocampus (Li et al, 2011;Takano et al, 2012;Zhang et al, 2012). Although the underlying mechanisms remain unidentified, it has been reported that glucocorticoids can prevent synaptic function maturation through suppression of the BDNF-stimulated MAPK/ERK pathway (Kumamaru et al, 2011(Kumamaru et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this observation, previous studies have reported an upregulation of BDNF expression and secretion in response to lamotrigine treatment. 52,53 It should be noted, however, that in this crosssectional case-control study, we were not able to rule out the possibility that higher CSF concentration of SgII is associated with a subset of patients with bipolar disorder treated with lamotrigine as opposed to other medication. 54 …”
Section: Discussionmentioning
confidence: 69%
“…Chronic stress-induced spatial memory impairment is attenuated by chronic lithium treatment (Vasconcellos et al, 2003). Chronic or subchronic treatment with lamotrigine ameliorates behavioral parameters in stress-induced animal models of depression with concomitant restoration of stress-induced downregulation of neuroprotective proteins (N. Li et al, 2010;N. Li et al, 2011).…”
Section: Resultsmentioning
confidence: 99%